THE ANALYSIS OF SARTRE’S ‘ESSENCE’ AND ‘SUBJECTIVITY’ IN DISNEY PIXAR’S SOUL ANIMATION - Putri Rindu Kinasih (Journal of English Language and Culture, 2021)
From the start, the philosophical movement that came to be known as existentialism was associated with literature. This possibility happens because there is a natural affinity between existential philosophy and narrative forms of art. On one hand, existentialist concur on the primacy of individual existence, of the lived experience of concrete human beings. On the other hand, cinematic narratives tell stories of beings such as ourselves, helping us to make sense of our existence and opening up probabilities that we might never have pondered otherwise (Shaw, 2017). Interestingly, Time.com stated that Pixar films are the philosophical of the animation world. Here lies the reason why the writer decided to analyze the portrayal of Jean-Paul Sartre’s famous phrase ‘Existence Precedes Essence’ in the latest Disney Pixar animation, Soul. Sartre argued that for human beings, our existence precedes our essence. In addition, Sartre’s notion of ‘existence’ characterized in terms of consciousness, free choice and ‘subjectivity’. For Sartre, the first act of consciousness is to choose. This study shows that Disney Pixar’sSoul does portray Sartre’s ‘existence precedes essence’ through Joe’s life – human beings have no fixed preordained essence or definition. Moreover, Sartre’s idea of consciousness or subjectivity can be seen from 22’s decision to be dared to live.